พอลิบิวทิลีนซักซิเนต/แอลฟาเซลลูโลสคอมพอสิตที่เสริมสภาพเข้ากันได้ด้วยไกลซิดิลเมทาคริเลตกราฟต์พอลิบิวทิลีนซักซิเนต - สฤษฎ์ ลิประพันธ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
The aims of this research are to prepare and investigate properties of composites from bioplastics those are poly(butylene succinate) reinforced with alpha cellulose in the presence of glycidyl methacrylate grafted poly(butylene succinate). Initially, the grafting of poly(butylene succinate) with glycidyl methacrylate was carried out in a twin-screw extruder. The obtained glycidyl methacrylate grafted poly(butylene succinate) was analyzed with Fourier transform infrared spectroscopy and volumetric analysis. Although the FTIR spectogram indicated slightly change, the titration technique confirmed the existence of around 3% of glycidyl methacrylate grafting on poly(butylene succinate). Subsequently, poly(butylene succinate), alpha cellulose (0, 2, 4, 6, 8 and 10 parts per a hundred of resin, phr), and glycidyl methacrylate grafted poly(butylene succinate) (0, 5 and 10 phr) were melt-mixed in a twin-screw extruder. The obtained compounds were processed into test specimens by the injection molding process. The effects of amounts of the filler and the compatibilizer on mechanical properties, thermal properties and water absorbancy of poly(butylene succinate) composites were studied. It was found that, without the compatibilizer, when the amount of alpha cellulose increased, the mechanical properties and thermal stability decreased comparing with neat poly(butylene succinate). The water absorbent increased. When the compatibilizer was incorporated, the overall mechanical properties increased due to enhanced interaction between poly(butylene succinate) and alpha cellulose. Furthermore, the crystalline melting and crystallization temperatures slightly increased while the compatibilizer limited water accessibility in the composites. The results indicated that the optimum ratio for preparing such bioplastic composites was when the amounts of alpha cellulose and glycidyl methacrylate grated poly(butylene succinate) were 6 and 10 phr, respectively.